Fotografía española en Marruecos: realidades soñadas, ensoñaciones recreadas - José Luis Gómez Barceló (Mélanges de la Casa de Velázquez, 2007)
Going back to the simultaneous origins of orientalism and photography, this article claims for the latter its own dimension of orientalist art whose authors not only found in Morocco a setting in which to realise their dreams but actually succeeded in recreating them. In the nineteenth-century, photographic orientalism was normally practiced by travellers; in the 20th century it became the domain of professionals residing in the Protectorate, who worked with the powers that be to create an image in the service of State propaganda. These and many amateur photographers have been rescued from oblivion thanks to the study of images in both public and private collections.